Exergy analysis of electrodialysis for water desalination: Influence of irreversibility sources. (15th April 2022) - Giacalone, F.; Catrini, P.; Gurreri, L.; Tamburini, A.; Cipollina, A.; Micale, G.; Piacentino, A.
Highlights: An exergy analysis of the electrodialysis process for water desalination is performed. Brackish Water, Concentrated Brackish Water and Seawater were considered as feed solutions. All irreversible phenomena within the unit are described using a 1-D model. The impact of IEMs resistance on exergy efficiency is evaluated. Exergy efficiency of electrodialysis is strongly affected by feed concentration. Double stage systems have higher exergy efficiency and lower SEC than single stage ones. Abstract: The increasing freshwater demand is pushing the development and adoption of desalination technologies. In this framework, electrodialysis has a consolidated role in brackish water desalination, but to make it competitive with other technologies for the desalination of more concentrated solutions ( e.g., seawater), the specific energy consumption should be reduced. Exergy analysis provides a useful tool for determining the contribution of each thermodynamic inefficiencies on the process efficiency and the specific energy consumption. In this regard, this paper presents an exergy analysis of the electrodialysis process. A 1-D model is used for evaluating the performance of industrial-scale systems, consisting of a single or a double-stage configuration, and fed by brackish water, concentrated brackish water, or seawater. The analysis is devoted to quantifying the effects of irreversibility sources, focusing especially on the non-ideal membrane behavior. Results highlight that the ohmic resistance of solutions and membranes along with undesired transport phenomena play a major role. More specifically, passing from an "ideal" to a "real" process, the maximum value of the exergy efficiency decreases by about 6% in the case of brackish water and 16% in the case of seawater. Besides, results reveal that the water permeability of membranes is detrimental to the exergy efficiency, leading to an 8% reduction in the case of seawater desalination. The development of improved membranes with low resistances slightly enhances the exergy efficiency with negligible influence on the performance of the system. The adoption of the double-stage strongly reduces the specific exergy consumption, and in the second stage, the exergy destruction due to uncontrolled mixing phenomena becomes more important than the one caused by the membrane resistance. The results shed a light on the main actions to be undertaken by industries and engineers for improving the performance of electrodialysis systems.